AMD3100 protects from UV-induced skin cancer - Byrne, Scott N.; Sarchio, Seri Narti Edayu (Taylor & Francis, 2014)
Sunlight causes skin cancer by directly damaging DNA as well as by suppressing antitumor immune responses. A major mechanism whereby sunlight exerts immunosuppressive effects is by modulating the migration of chemokine (C-X-C motif) receptor 4 (CXCR4)-expressing dermal mast cells into and away from the skin. We have demonstrated the importance of this by showing that the systemic administration of the CXCR4 antagonist AMD3100 prevents sunlight-induced immunosuppression as well as the consequent carcinogenic response. Our results highlight the therapeutic potential of antagonizing CXCR4 signaling, especially in individuals who are at high risk of developing skin cancer.